Container terminal competition and cooperation considering emission tax. Issue 7 (3rd October 2022) - Wang, Jian; Huang, Qi; Lin, Xudong; Yu, Mingzhu
ABSTRACT: This paper studies the competition and cooperation problem in a regional port system with two container terminals. Two game models are proposed to analyze the decisions of container terminal operators and the local government, respectively. We consider the emission tax, container terminal's service level and service price and derive the optimal decisions of the players. From the numerical analysis results, we find that in the regional port system, (1) a relatively developed container terminal is a good choice for consumers who prefer high-quality and efficient service, while those whose main concern is price can choose a developing container terminal; (2) for the benefit of all players, cleaner fuels should be used to decrease the proportion of unit pollution emission; (3) if social welfare is more emphasized than environmental protection, competition between the two container terminals is preferred, otherwise, cooperation is more beneficial.